SOME ASPECTS OF USING EXPRESSIVE ARTS-THERAPIES IN EDUCATION AND REHABILITATION - Martinec, Renata (Specijalna edukacija i rehabilitacija, 2013)
In this article, contemporary approaches in different fields of expressive arts-therapies (art therapy, music therapy, dance movement therapy, bybliotherapy, psychodrama and drama therapy) and bibliotherapy) are presented. Also, fundamental settings of each of these fields are described such us: historical and theoretical background, observation and assessment elements, as well as methods and therapeutic influence in the frame of individual or group process. In that way some relevant knowledge about different aspects of expressive art-therapies are presented by reviewing some recent references and results of different investigations. According to the theoretical and empirical background, the using of expressive arts-therapies as therapeutic, complementary and supportive methods in different problem fields of education and rehabilitation is considered.